2008
DOI: 10.1196/annals.1410.020
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐specific Prenatal Programming

Abstract: Women are four to eight times more likely to be affected by fibromyalgia syndrome (FMS). A lack of cortisol, potentially due to an adrenocortical deficit is postulated in FMS. The cause of such adrenal insufficiency is unknown. It could be assumed that stress exposure during critical periods contributes to vulnerability for FMS. These critical periods might include prenatal periods in which adversities may lead to an impaired development of the adrenal cortex, especially in females. More than 50% of FMS patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…However, whether chronic stress outside of the laboratory may serve as an ‘opportunity’ to translate dysfunctional stress reactivity into FSS has received little attention so far. A recent study conducted in women with fibromyalgia revealed a shorter gestational length (another indicator of early life stress) to be related to altered neuroendocrine stress reactivity, while at the same time 70% of the sample reported severe stress as a triggering event for their symptoms [74] . Unfortunately, the authors did not report to what extent these events were only present in the early life stress/altered stress reactivity group.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether chronic stress outside of the laboratory may serve as an ‘opportunity’ to translate dysfunctional stress reactivity into FSS has received little attention so far. A recent study conducted in women with fibromyalgia revealed a shorter gestational length (another indicator of early life stress) to be related to altered neuroendocrine stress reactivity, while at the same time 70% of the sample reported severe stress as a triggering event for their symptoms [74] . Unfortunately, the authors did not report to what extent these events were only present in the early life stress/altered stress reactivity group.…”
Section: Discussionmentioning
confidence: 99%
“…Salivary free cortisol output may be similar or higher in FMS patients compared to healthy subjects [333,340,341], while the cortisol awakening response (i.e., the rise in cortisol concentrations in the first hour after awakening) can be normal or diminished [340,342,343]. Total and free cortisol concentrations may be dissociated in FMS patients.…”
Section: Stress the Hpa Axis And The Autonomic Nervous Systemmentioning
confidence: 99%
“…42,43 The evidence that physical trauma influence FM development in adulthood results from studies where the impact of early life pain experiences was evaluated: Early and childhood experiences have been associated with long-lasting changes in nociceptive circuitry and increases pain sensitivity in the older organism. 44 For example, adverse events during the neonatal and childhood life, like premature birth, 45 physical and sexual abuse, 46,47 have been shown to possibly contribute to an alteration of threshold pain in adulthood and the development of FM onset. 48 As result of stress events, an impairment of HPA (hypothalamic-pituitary-adrenal) axis could rise up, with a subsequent inefficient response to stress and enhanced sensitivity to pain and fatigue.…”
Section: Environmental Influences On the Occurrence Of Fmmentioning
confidence: 99%